Metode Outdoor Study Dalam Pembelajaran Ilmu Pengetahuan Alam (IPA) Terhadap Motivasi Belajar Siswa Kelas IV MIN 2 Pandeglang - widi astuti; anggi solihah; agus hidayatullah (STKIP Paris Barantai, 2023)
Abstract This research is motivated by the low learning motivation of class IV students at MIN 2 Pandeglang in science subjects, due to the lack of interest of students in the environment. The formulation of the problem in this study is how effective the outdoor study method is in motivating learning for class IV students of Pandeglang MIN 2 in science learning. This study aims to determine and analyze the effectiveness of the outdoor study method in motivating learning for fourth grade students at Min 2 Pandeglang. This type of research uses the interview method. The research population was the teachers of class IV MIN 2 Pandeglang. The results of this interview tell us that the outdoor study method has proven effective on the learning motivation of fourth grade students at MIN 2 Pandeglang by obtaining an average daily test score of 65 and obtaining an average PTS score of 80. So it can be concluded that the outdoor study method can increase student learning motivation class IV min 2 Pandeglang. Keywords: outdoor study method, learning motivation